Influence of Poly(L-Lactic Acid) Nanofibers and BMP-2–Containing Poly(L-Lactic Acid) Nanofibers on Growth and Osteogenic Differentiation of Human Mesenchymal Stem Cells - Markus D. Schofer; Susanne Fuchs-Winkelmann; Christian Gräbedünkel; Christina Wack; Roland Dersch; Markus Rudisile; Joachim H. Wendorff; Andreas Greiner; Jürgen R. J. Paletta; Ulrich Boudriot (The Scientific World Journal)
The aim of this study was to characterize synthetic poly-(L-lactic acid) (PLLA) nanofibers concerning their ability to promote growth and osteogenic differentiation of stem cells in vitro, as well as to test their suitability as a carrier system for growth factors. Fiber matrices composed of PLLA or BMP-2–incorporated PLLA were seeded with human mesenchymal stem cells and cultivated over a period of 22 days under growth and osteoinductive conditions, and analyzed during the course of culture, with respect to gene expression of alkaline phosphatase (ALP), osteocalcin (OC), and collagen I (COL-I). Furthermore, COL-I and OC deposition, as well as cell densities and proliferation, were analyzed using fluorescence microscopy. Although the presence of nanofibers diminished the dexamethasone-induced proliferation, there were no differences in cell densities or deposition of either COL-I or OC after 22 days of culture. The gene expression of ALP, OC, and COL-I decreased in the initial phase of cell cultivation on PLLA nanofibers as compared to cover slip control, but normalized during the course of cultivation. The initial down-regulation was not observed when BMP-2 was directly incorporated into PLLA nanofibers by electrospinning, indicating that growth factors like BMP-2 might survive the spinning process in a bioactive form.